Topical Vs Pribulbar Anesthesia in Patients Undergoing 23 Guage ,Three Ports Removal of Sillicone Oil - Muhammad Hamza Shahid, Faisal Rashid, Saba Tauqeer, Rabab Ali, Muhammad Talha Farooq, Nouman Aleem (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare safety as well as efficacy of topical anesthesia against peribulbar anesthesia for patients undergoing three ports pars plana removal of silicone oil . Background: Silicone oil is used as a temponarding agent for vitreoretinal procedures and have to be removed according to the duration of temponard required as it is associated with complications like development and acceleration of cataract devlopment , secondary open angle glaucoma and corneal decompensation. It can be removed via three port 23 gauge ROSO procedure both under topical and peribulbar anesthesia. Patients & Methods: 40 eyes from 40 patients who underwent three port ROSO with a 23 gauge port system were randomised into two groups of 20 patients each for this study. In group A eyes was operated under topical anesthesia using soaked cotton wisk with 0.5 % proparacaine hydrochloride , placed for five minutes in superior and inferior fornix before the start of surgery and the group B was operated under peri bulbar block with 4 ml of bupivacaine given five minutes before the start of surgical procedure. Pain scoring charts were used by patients to rate their pain after the procedure. Results: The patients in this study had a mean age of 58.46 ±3.62 years, with a range of 30-65 years. 40 individuals were treated, with 26 being male and 14 being female. The mean pain score for patients in topical anesthesia group was 3.8+- 0.5 and the mean pain score in peribulbar block group was 2.2+-0.2 with a p value of 0.01. Conclusion: Peribulbar block is superior to topical anesthesia in patient comport for patients undergoing three port ROSO procedures. Keywords: ROSO, Silicone oil, peribulbar, Topical anesthesia, Bupicaine, Proparacaine hydrochloride.